2005
DOI: 10.1073/pnas.0506462102
|View full text |Cite
|
Sign up to set email alerts
|

Bicoid cooperative DNA binding is critical for embryonic patterning in Drosophila

Abstract: Cooperative interactions by DNA-binding proteins have been implicated in cell-fate decisions in a variety of organisms. To date, however, there are few examples in which the importance of such interactions has been explicitly tested in vivo. Here, we tested the importance of cooperative DNA binding by the Bicoid protein in establishing a pattern along the anterior-posterior axis of the early Drosophila embryo. We found that bicoid mutants specifically defective in cooperative DNA binding fail to direct proper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 51 publications
7
99
0
Order By: Relevance
“…Also, cooperative binding of Bcd to target genes has been shown. 9,10 In this case, the binding of Bcd to a high affinity site would promote the binding of Bcd to a low affinity site in the vicinity.…”
Section: Bicoidmentioning
confidence: 99%
“…Also, cooperative binding of Bcd to target genes has been shown. 9,10 In this case, the binding of Bcd to a high affinity site would promote the binding of Bcd to a low affinity site in the vicinity.…”
Section: Bicoidmentioning
confidence: 99%
“…Therefore, Bcd binding to a high-affinity site potentiates binding to an adjacent low-affinity site (Burz et al, 1998). Expression of a Bcd protein with a mutation that disrupts cooperativity in the embryo leads to an anterior shift in the expression patterns of target genes, such as hb, and reduced sharpness of their posterior borders (Lebrecht et al, 2005).…”
Section: Combinatorial Inputsmentioning
confidence: 99%
“…Therefore, Bcd binding to a high-affinity site potentiates binding to an adjacent low-affinity site (Burz et al, 1998). Expression of a Bcd protein with a mutation that disrupts cooperativity in the embryo leads to an anterior shift in the expression patterns of target genes, such as hb, and reduced sharpness of their posterior borders (Lebrecht et al, 2005).The integration of inputs from Dl and from other transcription factors also influences the response of genes along the DV axis of the Drosophila embryo. An analysis of Dl target gene enhancers in different Drosophilids (Papatsenko and Levine, 2005) has revealed that, just as type I threshold genes tend to have lower Dl affinity than do type II genes, there is a similar trend in these promoters for the affinity of another transcription factor, Twi.…”
mentioning
confidence: 99%
“…This gradient determines the boundary of expression of downstream effectors such as Hunchback, eventually leading to the establishment of the segmented body plan. The dynamics of Bicoid pattern formation were recently studied in several experiments (8)(9)(10)(11)(12)(13)(14)(15). The gradient was found to have, to a good approximation, an exponential decay with distance from the anterior.…”
mentioning
confidence: 99%